High-density yeast-tiling array reveals previously undiscovered introns and extensive regulation of meiotic splicing - Juneau, Kara (National Academy of Sciences, 2007)
Knowing gene structure is vital to understanding gene function, and accurate genome annotation is essential for understanding cellular function. To this end, we have developed a genome-wide assay for mapping introns in Saccharomyces cerevisiae. Using high-density tiling arrays, we compared wild-type yeast to a mutant deficient for intron degradation. Our method identified 76% of the known introns, confirmed 18 previously predicted introns, and revealed 9 formerly undiscovered introns. Furthermore, we discovered that all 13 meiosis-specific intronic yeast genes undergo regulated splicing, which provides posttranscriptional regulation of the genes involved in yeast cell differentiation. Moreover, we found that ≈16% of intronic genes in yeast are incompletely spliced during exponential growth in rich medium, which suggests that meiosis is not the only biological process regulated by splicing. Our tiling-array assay provides a snapshot of the spliced transcriptome in yeast. This robust methodology can be used to explore environmentally distinct splicing responses and should be readily adaptable to the study of other organisms, including humans.